Strength and toughness of clean nanostructured bainite. Issue 10 (3rd July 2017) - Peet, M. J.; Fielding, L. C. D.; Hamedany, A. A.; Rawson, M.; Hill, P.; Bhadeshia, H. K. D. H.
ABSTRACT: A nanostructured steel has been produced using a clean steel-making technique. The mechanical properties have been comprehensively characterised. The maximum strength of the material recorded was 2.2 GPa at yield, with an ultimate tensile strength of 2.5 GPa, accompanied by a Charpy impact energy of 5 J, achieved by heat treatment to refine the prior austenite grain size from 145 to 20 µm. This increased the strength by 40% and the Charpy V-notch energy more than doubled. In terms of resistance of the hardness to tempering, the behaviour observed was similar to previous alloys. Despite reducing the hardness and strength, tempering was observed to reduce the plane-strain fracture toughness.